Increased proportion of nitric oxide synthase immunoreactive neurons in rat ileal myenteric ganglia after severe acute pancreatitis - Lin Zhong; Liu Ying; Zheng Qinghua; Hu Qinghua (BMC Gastroenterology, 2011)
Abstract Background Severe acute pancreatitis (SAP) remains a potentially life-threatening disease. Gastrointestinal motility disturbance such as intestinal ileus is seen in every case. By now, the mechanisms of pancreatitis-induced ileus are largely unknown. The main purpose of the present study was to observe changes of nitric oxide synthase-immunoreactive (NOS-IR) neurons in ileal myenteric ganglia in SAP rats with gastrointestinal dysmotility, trying to explore underlying nervous mechanisms of pancreatitis-induced ileus. Methods Twenty Sprague Dawley rats were randomly divided into sham operated group and SAP group. SAP was induced by retrograde cholangiopancreatic duct injection of 5% sodium taurocholate. Abdominal X-ray and intestinal transit were performed to detect the existence of paralytic ileus and intestinal dysmotility. Pathological damage of pancreas was evaluated. Double-immunolabeling was employed for the whole-mount preparations of ileal myenteric ganglia. The morphology of NOS-IR neurons were observed and the percentage of NOS-IR neurons was calculated based on the total Hu-immunoreactive neurons. Total RNA of ileum was extracted according to Trizol reagent protocol. Neuronal NOS (nNOS) mRNA expression was evaluated by RT-PCR. Results The small intestinal transit index in the SAP group was significantly lower compared with the sham operated group (29.21 ± 3.68% vs 52.48 ± 6.76%, P <0.01). The percentage of NOS-IR neurons in ileal myenteric ganglia in the SAP group was significantly higher than that in the sham operated group (37.5 ± 12.28% vs 26.32 ± 16.15%, P <0.01). nNOS mRNA expression in ileum of SAP group was significantly higher than that in the sham operated group (1.02 ± 0.10 vs 0.70 ± 0.06, P < 0.01). Conclusions The increased quantity of NOS-IR neurons in ileal myenteric ganglia and increased nNOS mRNA expression may suggest nNOS over expression as one of the nervous mechanisms of gastrointestinal dysmotility in SAP rat.